Transformation of the linear difference equation into a system of the first order difference equations - Ayzatsky, M.I. (Вопросы атомной науки и техники, 2019)
The transformation of the N-th-order linear difference equation into a system of the first order difference equations is presented. The proposed transformation opens possibility to obtain new forms of the N-dimensional system of the first order equations that can be useful for the analysis of solutions of the N-th-order difference equations. In particular for the third-order linear difference equation the nonlinear second-order difference equation that plays the same role as the Riccati equation for second-order linear difference equation is obtained. The new form of the Ndimensional system of first order equations can also be used to find the WKB solutions of the linear difference equation with coefficients that vary slowly with index. Представлено перетворення лінійного різницевого рівняння N-го порядку в систему різницевих рівнянь першого порядку. Запропонована трансформація відкриває можливість отримання нових форм N-вимірної системи рівнянь першого порядку, які можуть бути корисними для аналізу рішень різницевих рівнянь N-го порядку. Зокрема, для лінійних різницевих рівнянь третього порядку отримано нелінійне різницеве рівняння другого порядку, яке відіграє ту ж саму роль, що й рівняння Ріккаті для лінійного різницевого рівняння другого порядку. Нова форма N-вимірної системи рівнянь першого порядку також може бути використана для пошуку ВКБ-рішень лінійного різницевого рівняння з коефіцієнтами, які повільно змінюються з індексом. Представлено преобразование линейного разностного уравнения N-го порядка в систему разностных уравнений первого порядка. Предложенное преобразование открывает возможность получения новых форм N-мерной системы уравнений первого порядка, которые могут быть полезны для анализа решений разностных уравнений N-го порядка. В частности, для линейного разностного уравнения третьего порядка получено нелинейное разностное уравнение второго порядка, которое играет ту же роль, что и уравнение Риккати для линейного разностного уравнения второго порядка. Новая форма N-мерной системы уравнений первого порядка также может быть использована для нахождения ВКБ-решений линейного разностного уравнения с коэффициентами, которые медленно меняются в зависимости от индекса.